2016
DOI: 10.4238/gmr.15038264
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ADAMTS4 and ADAMTS5 are not linked to susceptibility to knee osteoarthritis in the Turkish population

Abstract: ABSTRACT. Considering the functions of aggrecanase-1 (ADAMTS4) and -2 (ADAMTS5), which are thought to be the two major enzymes responsible for the destruction of aggrecans in arthritic diseases, we investigated whether important polymorphisms in the ADAMTS4 and ADAMTS5 genes affect osteoarthritis (OA) susceptibility. Our study took place in Mugla, Turkey. Ninety-five cases were recruited following OA diagnosis (72 women and 23 men), and 80 individuals without any symptoms or radiographic signs of OA (56 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
(33 reference statements)
1
15
0
1
Order By: Relevance
“…The diagnosis of LDD was made based upon the confirmation of MRI scanning. There were seven studies [ 37–39 , 41–43 ] looking at ADAMTS5, one looking at only ADAMTS4 [ 40 ], and one focusing on both of them [ 44 ]. The rs2830585 and rs226794 SNPs in ADAMTS5 were the mostly frequently investigated polymorphisms among these studies, consequently we combined the ORs from each individual study using an allele genetic model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of LDD was made based upon the confirmation of MRI scanning. There were seven studies [ 37–39 , 41–43 ] looking at ADAMTS5, one looking at only ADAMTS4 [ 40 ], and one focusing on both of them [ 44 ]. The rs2830585 and rs226794 SNPs in ADAMTS5 were the mostly frequently investigated polymorphisms among these studies, consequently we combined the ORs from each individual study using an allele genetic model.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects with TT genotype also had significantly lower risk of LLD than subjects with CC genotype (OR 0.21, 95%CI 0.0461, 0.99; P =0.0374). Canbek et al’s study [ 44 ] investigated rs226794 and rs2830585. For them, neither genotype nor allele distribution was observed to have an association with KOA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two missense SNPs (rs226794 and rs2830585) in ADAMTS5 were predicted to be deleterious for ADAMTS5 protein function using the SIFT database. The associations between ADAMTS5 gene polymorphisms and OA risk have been investigated in three studies, but with conflicting findings (1214). Rodriguez-Lopez et al (12) firstly evaluated the association between ADAMTS5 rs226794 polymorphism and OA risk in 4 Caucasian groups, and found that this polymorphism decreased the risk of knee OA in the Santiago and Thessaly groups (872 cases and 974 controls), but not in the Oxford and Corunna groups.…”
Section: Discussionmentioning
confidence: 99%
“…The function of ADAMTS5 may be influenced by two non-synonymous single nucleotide polymorphisms (SNPs) by altering the amino acid sequence of the protein. The association of ADAMTS5 gene variants [rs226794 (P692L in exon 7) and rs2380585 (R614H in exon 5)] with OA development has been studied in various populations (1214), but not in East China. Therefore, the present study was conducted to evaluate the effects of ADAMTS5 gene polymorphisms on OA risk in an East Chinese Han Population.…”
Section: Introductionmentioning
confidence: 99%